EU-CERT - European Certificates and Accreditation for European Projects. The EU-CERT – Accreditation Conference. Insight into PR1: EU-CERT - Research on Quality Criteria, Accreditation and Certificate Structures - Schneider, Jennifer Nicole

European Certificates and Accreditation for European Projects. The EU-CERT-Project – Insight into PR1: EU-CERT - Research on Quality Criteria, Accreditation and Certificate Structures - Beutner, Marc; Schneider, Jennifer Nicole

EU-CERT - European Certificates and Accreditation for European Projects. The EU-CERT-Project - Insight into PR2: EU-CERT - Concept Design for Accreditation and Certification Processes - Beutner, Marc; Schneider, Jennifer Nicole

EU-CERT - European Certificates and Accreditation for European Projects. The EU-CERT-Project - Insight into PR4: EU-CERT - Accreditation Handbook - Beutner, Marc; Schneider, Jennifer Nicole

EU-CERT. Second Transnational Project Meeting.Presentation about accreditation and certificate structures - Schneider, Jennifer Nicole

STEMinAction: Open Educational Resource Workshop - Schneider, Jennifer Nicole

OERCamp. Barcamp Sessions zu OER in der berufl. Bildungsforschung - Schneider, Jennifer Nicole

E-Learning, Digitisation and Units for Learning at VET schools Creating Online Learning Environments in Technical Education for European metal industry. New Opportunities and Challenges for European VET schools in metal industry. Insights in the EDU VET Project

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Open Educational Resources – Sustainability in green Start-ups! - Schneider, Jennifer Nicole

EU-CERT - European Certificates and Accreditation for European Projects. The EU-CERT – Accreditation Conference. Current Status of the EU-CERT project - Schneider, Jennifer Nicole

EU-CERT - European Certificates and Accreditation for European Projects. The EU-CERT-Project - Dissemination and Exploitation - Beutner, Marc; Schneider, Jennifer Nicole

Family Business Library. Rural and Regional Libraries as Local family Entrepreneurship Centers. Policy Paper - Schneider, Jennifer Nicole

EU-CERT - European Certificates and Accreditation for European Projects - Beutner, Marc; Schneider, Jennifer Nicole

EU-CERT - European Certificates and Accreditation for European Projects - Schneider, Jennifer Nicole

Alles wird gut, immer (Rezension) - Lammer, Christina (KinderundJugendmedien.de)

Preserving, Restoring, and Passing Down Video-Game Music from the Past: The Case of Directmusic - Ludovico, Luca A.; Mattea, Alberto; Mauro, Davide Andrea (Proceedings of the 19th Sound and Music Computing Conference, June 5-12th, 2022, Saint-Étienne (France))

Ethan D. Bolker und Maura B. Mast: Common Sense Mathematics, Second Edition. AMS/MAA Press 2021 - Hilgert, Joachim (Mathematische Semesterberichte)

Engagement, Ehrenamt und Digitalisierung während der Corona-Krise im Bereich des Immateriellen Kulturerbes. Gesellschaftliche Rituale, Bräuche und Feste und die Folgen von Covid-19 - Leineweber, Jonas (Heimat Westfalen)

Schützenfeste@home und "gesicherte Brauchtumszonen". Eine ‚Geschichte in Echtzeit‘ von Ritualen, Bräuchen und Festen in der Coronakrise - Leineweber, Jonas (Westfalen/Lippe - historisch)

Theoriepolitiken des Überlebens: Trauerarbeit mit Lauren Berlant - Degeling, Jasmin; Hohmann, Philipp (Texte zur Kunst 126. Trauern. Mourning)

Die Evaluation des Modellschulprojekts ‚Lernen mit digitalen Medien an Förderzentren Geistige Entwicklung/Körperlich-Motorische Entwicklung‘ in Schleswig-Holstein - Gerick, J.; Steglich, E.; Eickelmann, Birgit; Oelkers, J. (Zeitschrift Die Deutsche Schule)

Relevance of Pre-Service Teacher Training to use ICT for the Actual Use in Classrooms – Focus on German Secondary Schools. Technology, Pedagogy and Education - Lorenz, R.; Heldt, M.; Eickelmann, Birgit (Journal for Technology, Pedagogy and Education)

International Computer and Information Literacy Study 2018 (ICILS 2018) (Version 1) [Datensatz]. Berlin - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie

Charakterisierung von Schüttschichtmaterialien für den Einsatz in Filtern für häusliche Holzfeuerungsanlagen (Studienarbeit) - Schlattmann, Ulrich; Beimdiek, Janis

Innovative Lehre = kreative Lernende? Beforschung eines kunstdidaktischen Lehr-Lernkonzepts - Schmidt, Rebekka; Theis, Julia (Hochschullehre erforschen)

Kunstdidaktik vernetzen. Ein Fortbildungskonzept für Kunstlehrkräfte - Schmidt, Rebekka; Waffner-Labonde, Annika; Welzel, Jana (Kunst- und Musikunterricht im digitalen Wandel. Konzepte und Materialien für die Lehrer*innenaus- und weiterbildung. Themenheft der Zeitschrift DiMawe – Die Materialwerkstatt)

Inklusion braucht Begegnung. Bereits in der Lehrkräftebildung die Grundlagen für gelingende Inklusion anbahnen - Schmidt, Rebekka (Die Bildung Aller – Kunstpädagogik und Inklusion)

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)

Inklusion im Kunstunterricht - Schmidt, Rebekka (Lexikon der Kunstpädagogik)

Online-Videokonferenzen als virtueller Lernraum für Fremdsprachenlernende und Fremdsprachenlehrende - Prikoszovits, Matthias

(De)Coding social practice in the field of XAI: Towards a co-constructive framework of explanations and understanding between lay users and algorithmic systems - Finke, Josefine; Horwath, Ilona; Matzner, Tobias; Schulz, Christian (Artificial Intelligence in HCI)

Reziprozität und das alteritäre Dritte – Über die wechselseitigen Verflechtungen von PageRank und sozialen Medien - Schulz, Christian (Behemoth . A Journal on Civilisation)

Mediale Fluidität oder fluide Medialität? Eine kurze Geschichte des Social-Media-Feeds - Schulz, Christian; Allekotte, Ann-Kathrin (Fluide Mediale. Medialität, Materialität und Medienästhetik des Fluiden)

INVESTIGATION OF THE PROCESS PARAMETERS AND GEOMETRY DEPENDENT SHRINKAGE BEHAVIOR OF RASTER LINES IN THE FUSED DEPOSITION MODELING PROCESS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

Perspektiven feministischer Digitalisierungsforschung: Querschnittsthemen gesellschaftlicher Transformation im komplexen Zusammenspiel - Richter, Susanne (Feminismen in der Sozialen Arbeit. Debatten, Dis/Kontinuitäten, Interventionen)

Hierarchischen Ordnungen auf der Spur in digitalen Räumen - Richter, Susanne (Freie Assoziation)

YouTube, Männlichkeiten und die Genese von Körpern. Geschlechteranalytische und erziehungswissenschaftliche Einsätze - Hoffarth, Britta; Richter, Susanne; Wehren, Sylvia (Materialität – Digitalisierung – Bildung)

Christian Thiel, Fregeana. Zwölf Studien über Freges Logik
XII + 247 S. Rezension: Dókos. Revista filosófica 31–32 (2023), 275–281 (J. Padilla Gálvez)

Nachhaltige Softwareentwicklung - Von der Inhouse-Lösung zur Open Source-Community am Beispiel von MerMEId - Henny-Krahmer, Ulrike; Stadler, Peter

Banking the Future of Banking: Savings banks and the Digital Age in East and West Germany - Schmitt, Martin (Prophets of Computing: Visions of Society Transformed by Computing)
Keywords: Sparkassen; Computer; 1960er; Kreditwirtschaft; Digitalisierung; Deutschland {<}DDR{>}; Deutschland {<}Bundesrepublik{>}

Rezension zu: Fickers, Andreas/Griset, Pascal: Communicating Europe. Technologies, Information, Events, Basingstoke, Hampshire 2019 - Schmitt, Martin (Francia-Recensio)

Ausstellungsrezension: Back to Future. Technikvisionen zwischen Fiktion und Realität, 03.12.2021 – 28.08.2022 Berlin - Schmitt, Martin (H-Soz-Kult)

Tagungsbericht: Ethik der Digitalstadt - Herausforderung der Datensouveränität, 03.12.2021 – 03.12.2021 Darmstadt - Schmitt, Martin (H-Soz-Kult)

What is Missing in XAI So Far? - Schmid, Ute; Wrede, Britta (KI - Künstliche Intelligenz)
Abstract With the perspective on applications of AI-technology, especially data intensive deep learning approaches, the need for methods to control and understand such models has been recognized and gave rise to a new research domain labeled explainable artificial intelligence (XAI). In this overview paper we give an interim appraisal of what has been achieved so far and where there are still gaps in the research. We take an interdisciplinary perspective to identify challenges on XAI research and point to open questions with respect to the quality of the explanations regarding faithfulness and consistency of explanations. On the other hand we see a need regarding the interaction between XAI and user to allow for adaptability to specific information needs and explanatory dialog for informed decision making as well as the possibility to correct models and explanations by interaction. This endeavor requires an integrated interdisciplinary perspective and rigorous approaches to empirical evaluation based on psychological, linguistic and even sociological theories.
Keywords: Artificial Intelligence

Explainable AI - Schmid, Ute; Wrede, Britta (KI - Künstliche Intelligenz)
Keywords: Artificial Intelligence

AI: Back to the Roots? - Wrede, Britta (KI - Künstliche Intelligenz)
Keywords: Artificial Intelligence

Exploring Monological and Dialogical Phases in Naturally Occurring Explanations - Fisher, Josephine B.; Lohmer, Vivien; Kern, Friederike; Barthlen, Winfried; Gaus, Sebastian; Rohlfing, Katharina (KI - Künstliche Intelligenz)
Abstract Recent approaches to Explainable AI (XAI) promise to satisfy diverse user expectations by allowing them to steer the interaction in order to elicit content relevant to them. However, little is known about how and to what extent the explainee takes part actively in the process of explaining. To tackle this empirical gap, we exploratively examined naturally occurring everyday explanations in doctor–patient interactions ( N = 11). Following the social design of XAI, we view explanations as emerging in interactions: first, we identified the verbal behavior of both the explainer and the explainee in the sequential context, which we could assign to phases that were either monological or dialogical; second, we investigated in particular who was responsible for the initiation of the different phases. Finally, we took a closer look at the global conversational structure of explanations by applying a context-sensitive model of organizational jobs, thus adding a third layer of analysis. Results show that in our small sample of conversational explanations, both monological and dialogical phases varied in their length, timing of occurrence (at the early or later stages of the interaction) and their initiation (by the explainer or the explainee). They alternated several times in the course of the interaction. However, we also found some patterns suggesting that all interactions started with a monological phase initiated by the explainer. Both conversational partners contributed to the core organizational job that constitutes an explanation. We interpret the results as an indication for naturally occurring everyday explanations in doctor–patient interactions to be co-constructed on three levels of linguistic description: (1) by switching back and forth between monological to dialogical phases that (2) can be initiated by both partners and (3) by the mutual accomplishment and thus responsibility for an explanation’s core job that is crucial for the success of the explanation. Because of the explorative nature of our study, these results need to be investigated (a) with a larger sample and (b) in other contexts. However, our results suggest that future designs of artificial explainable systems should design the explanatory dialogue in such a way that it includes monological and dialogical phases that can be initiated not only by the explainer but also by the explainee, as both contribute to the core job of explicating procedural, clausal, or conceptual relations in explanations.
Keywords: Artificial Intelligence

Which “motionese” parameters change with children's age? Disentangling attention-getting from action-structuring modifications - Rohlfing, Katharina; Vollmer, Anna-Lisa; Fritsch, Jannik; Wrede, Britta (Frontiers in Communication)
Modified action demonstration—dubbed motionese— has been proposed as a way to help children recognize the structure and meaning of actions. However, until now, it has been investigated only in young infants. This brief research report presents findings from a cross-sectional study of parental action demonstrations to three groups of 8–11, 12–23, and 24–30-month-old children that applied seven motionese parameters; a second study investigated the youngest group of participants longitudinally to corroborate the cross-sectional results. Results of both studies suggested that four motionese parameters (Motion Pauses, Pace, Velocity, Acceleration) seem to structure the action by organizing it in motion pauses. Whereas these parameters persist over different ages, three other parameters (Demonstration Length, Roundness, and Range) occur predominantly in the younger group and seem to serve to organize infants' attention on the basis of movement. Results are discussed in terms of facilitative vs. pedagogical learning.
Keywords: Social Sciences (miscellaneous); Communication

Formalizing cognitive biases in medical diagnostic reasoning - Battefeld, Dominik; Kopp, Stefan (Presented at the 8th Workshop on Formal and Cognitive Reasoning (FCR), Trier.)
This paper presents preliminary work on the formalization of three prominent cognitive biases in the diagnostic reasoning process over epileptic seizures, psychogenic seizures and syncopes. Diagnostic reasoning is understood as iterative exploration of medical evidence. This exploration is represented as a partially observable Markov decision process where the state (i.e., the correct diagnosis) is uncertain. Observation likelihoods and belief updates are computed using a Bayesian network which defines the interrelation between medical risk factors, diagnoses and potential findings. The decision problem is solved via partially observable upper confidence bounds for trees in Monte-Carlo planning. We compute a biased diagnostic exploration policy by altering the generated state transition, observation and reward during look ahead simulations. The resulting diagnostic policies reproduce reasoning errors which have only been described informally in the medical literature. We plan to use this formal representation in the future to inversely detect and classify biased reasoning in actual diagnostic trajectories obtained from physicians.
Keywords: Diagnostic reasoning; Cognitive bias; Cognitive model; POMDP; Bayesian network; Epilepsy; CDSS

Modeling Feedback in Interaction With Conversational Agents—A Review - Axelsson, Agnes; Buschmeier, Hendrik; Skantze, Gabriel (Frontiers in Computer Science)
Intelligent agents interacting with humans through conversation (such as a robot, embodied conversational agent, or chatbot) need to receive feedback from the human to make sure that its communicative acts have the intended consequences. At the same time, the human interacting with the agent will also seek feedback, in order to ensure that her communicative acts have the intended consequences. In this review article, we give an overview of past and current research on how intelligent agents should be able to both give meaningful feedback toward humans, as well as understanding feedback given by the users. The review covers feedback across different modalities (e.g., speech, head gestures, gaze, and facial expression), different forms of feedback (e.g., backchannels, clarification requests), and models for allowing the agent to assess the user's level of understanding and adapt its behavior accordingly. Finally, we analyse some shortcomings of current approaches to modeling feedback, and identify important directions for future research.
Keywords: General Medicine

An Architecture Supporting Configurable Autonomous Multimodal Joint-Attention-Therapy for Various Robotic Systems - Groß, André; Schütze, Christian; Wrede, Britta; Richter, Birte (INTERNATIONAL CONFERENCE ON MULTIMODAL INTERACTION)

Enabling Non-Technical Domain Experts to Create Robot-Assisted Therapeutic Scenarios via Visual Programming - Schütze, Christian; Groß, André; Wrede, Britta; Richter, Birte (INTERNATIONAL CONFERENCE ON MULTIMODAL INTERACTION)

Modellbasierte Ermittlung optimaler Prozessparameter für neuartige Ultraschallbondverbindungen - Scheidemann, Claus; Hemsel, Tobias; Sextro, Walter

Editorial: Netzwerke und Vernetzung im Sport - Meier, Heiko; Kukuk, Marc; Riedl, Lars (Sport und Gesellschaft)
Keywords: Philosophy; Social Sciences (miscellaneous); History

Wissenschaftliches Publizieren als Grundlage und Gestaltungsfeld der Wissenschaftsbewertung - Deutsche Forschungsgemeinschaft | AG Publikationswesen, (DFG); Sureth-Sloane, Caren
Academic publishing represents one of the core functions of scientific activity and thus of the research system. The Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) is committed to the adequate communication of research results and the maintenance of a functioning publication system as a basic requirement of the research system. Ensuring that academic publishing serves foremost the purposes of publicising, quality review and documenting scientific findings should be an essential goal of responsible science administration and promotion. The position paper therefore analyses the central background of the current situation in scientific publishing, identifies challenges and points out possible fields of action. With this positioning, the DFG contributes to the further development of the publication system in a way that is appropriate for science and research.

Vereinzelung oder Gemeinschaftsbildung: Was passiert an Calisthenics-Anlagen? - Meier, Heiko; Kukuk, Marc; Schmieding, Ruben (Playground@Landscape)

Die Bedeutung und Funktion sportlicher Aktivitäten im Gesundheitsmanagement der öffentlichen Verwaltungen - Barrieren und Gelingensbedingungen. - Sennefelder, Lisa

Wie passen Vertrauen, Kontrolle und Hierarchie zusammen? Ein erlebnispädagogisch orientiertes Konzept zum Aufbau einer Vertrauenskultur in Verwaltungsorganisationen - Sennefelder, Lisa; Meier, Heiko

Vertrauen im Sport – mehr als nur ein No-Look-Pass - Meier, Heiko (Facetten des Vertrauens und Misstrauens)
Ohne ständig thematisiert zu werden, kommt Vertrauen im Sport immer eine große Bedeutung zu, sei es beim No-look-Pass, bei der Hilfestellung im Turnen oder im Klettersport. Mehr noch: Ohne Vertrauensgrundlage ist Sport praktisch oftmals unmöglich. Umgekehrt wiegen Vertrauensbrüche schwer. Sie gefährden Sportarten, Sportorganisationen und Personen. Damit ist der Aufbau von Vertrauen offensichtlich für den Sport konstitutiv. Der Beitrag untersucht deshalb, wie Vertrauen im Sport nicht nur soziale Verhältnisse und Beziehungen umrahmt, sondern sie konstituiert, und inwiefern sich der Sport diesbezüglich von anderen gesellschaftlichen Kontexten unterscheidet. Dazu wird unter Rückgriff auf Niklas Luhmanns Unterscheidung zwischen Person- und Systemvertrauen der Sportverein dahingehend analysiert, wie bedeutsam und wie funktional Vertrauen für dessen Selbstorganisation und Systemerhalt ist. Dies führt zu dem Vorschlag, Vertrauen im Sportverein als Steuerungsinstrument anzusehen, welches in einer spezifischen Symbolik zum Ausdruck kommt.

"Und dann muss es gelebt werden!" - Der Sport im Gesundheitsmanagement öffentlicher Verwaltungen - Sennefelder, Lisa

Vertrauen in der öffentlichen Verwaltung - Sennefelder, Lisa

METAdata and metaDATA - Ried, Dennis; Gubsch, Clemens
Metadata are a very broad and extremely differentiated subject and ranges from rudimentary catalog data to deeply indexed scientific catalogs (e.g., catalogs of works). In this paper, the concept of metadata in the context of MEI is first examined, before two examples are used to show that metadata are more than just rudimentary descriptions. These examples are also intended to illustrate the extent to which metadata are encoded in the field of music philology and thus represent an attempt to create a little more awareness for the work of the Metadata and Cataloging Interest Group of MEI. The examples deal on the one hand with the encoding of performance resources and on the other hand with watermarks. In both cases, the possibilities of metadata encoding with MEI version 4 are exhausted and it is discussed which steps are useful and necessary to create an even deeper, machine-readable structure so that these sub-fields of the MEI metadata can also be used for larger scientific purposes such as analyses.

Ein Blick auf: Gestaltung des Übergangs in die Kindertageseinrichtung im Bundesprogramm „Kita-Einstieg: Brücken bauen in frühe Bildung“ - Albers, Timm; Hoeft, Maike; Meusel, Sarah; Heberle, Kathrin

Argumentationsindikatoren im Deutschen und im Französischen - Kunert, Irene Dorothea
Wie sieht ein Argument aus und wie eine Konklusion? Diese Frage, die seit Jahrhunderten auf der Ebene der Logik, der Rhetorik und der Dialektik diskutiert wird, beschäftigt auch die moderne Sprachwissenschaft. Die sprachliche Ausgestaltung von Argumentation ist so vielfältig, wie es auch das Phänomen der Argumentation selbst ist. Eine neue Form der Kategorisierung und eine systematische Beschreibung der Vielfalt dieser Argumentationsindikatoren stehen im Zentrum der vorliegenden Studie. Die qualitative und quantitative Analyse ausgewählter Indikatoren des Deutschen und des Französischen gewährt neue Erkenntnisse im Bereich des Sprachvergleichs und der Übersetzungsforschung. Die Studie richtet sich an alle, die sich für die Themen Argumentation, Übersetzung und deutsch-romanischer Sprachvergleich interessieren.

Der Gebrauch deutscher und französischer metaargumentativer Verben in wissenschaftlichen Publikationen - Kunert, Irene Dorothea (Syntax in Fachkommunikation)

Agnostic Explanation of Model Change based on Feature Importance - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (KI - Künstliche Intelligenz)
Explainable Artificial Intelligence (XAI) has mainly focused on static learning tasks so far. In this paper, we consider XAI in the context of online learning in dynamic environments, such as learning from real-time data streams, where models are learned incrementally and continuously adapted over the course of time. More specifically, we motivate the problem of explaining model change, i.e. explaining the difference between models before and after adaptation, instead of the models themselves. In this regard, we provide the first efficient model-agnostic approach to dynamically detecting, quantifying, and explaining significant model changes. Our approach is based on an adaptation of the well-known Permutation Feature Importance (PFI) measure. It includes two hyperparameters that control the sensitivity and directly influence explanation frequency, so that a human user can adjust the method to individual requirements and application needs. We assess and validate our method’s efficacy on illustrative synthetic data streams with three popular model classes.
Keywords: Artificial Intelligence

Helmut Lachenmann and Karlheinz Stockhausen: String quartets between avant-garde and tradition - Adler, Luise (Vlado S. Milošević: Tradition as Inspiration. Thematic proceedings from the 2021 scientific conference)
Helmut Lachenmann and Karlheinz Stockhausen are often regarded as representatives of a negative attitude towards traditions of canonised European art music. In their compositional self-image they strive for renewal and innovative artistic work beyond established models. However, an examination of ego-documents and compositions reveals contradictions within this claim. The essay therefore examines both composers’ concepts of and their self-location within tradition. The aim is to show how a decided departure from historical structural principles as well as latent lines of tradition are effective in two works. Because of the special historical significance of the genre, two string quartets have been selected.

wiḥdat ad-Dīn (Einheit der Religionen) - Abdelrahem, Mohammed (At-Taʿāyuš wa-t-taʿāruf fī l-islām – mafāhīm muyassara (Zusammenleben und Kennenlernen im Islam - Einführungsbegriffe))
Keywords: Dialog der Religionen; interreligiöser Dialog; Komparative Theologie; Islam und Christentum

Transitivitätscharakteristika als Werkzeug in der systematischen qualitativen Metaphernanalyse - Karsten, Andrea; Schwede, Jana; Körber, Miriam; Scharlau, Ingrid (Die Praxis der systematischen Metaphernanalyse: Anwendungen und Anschlüsse)

Options for demand side management in biofuel production: A systematic review - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Operating window and flexibility of a lab-scale methanation plant - Herrmann, Felix; Grünewald, Marcus; Meijer, Tobias; Gardemann, Ulrich; Feierabend, Lukas; Riese, Julia (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Demand response scheduling using derivative-based dynamic surrogate models - Di Pretoro, Alessandro; Bruns, Bastian; Negny, Stéphane; Grünewald, Marcus; Riese, Julia (Computers & Chemical Engineering)
Keywords: Computer Science Applications; General Chemical Engineering

A Techno-Economic Assessment of Fischer–Tropsch Fuels Based on Syngas from Co-Electrolysis - Peters, Ralf; Wegener, Nils; Samsun, Remzi Can; Schorn, Felix; Riese, Julia; Grünewald, Marcus; Stolten, Detlef (Processes)
As a part of the worldwide efforts to substantially reduce CO2 emissions, power-to-fuel technologies offer a promising path to make the transport sector CO2-free, complementing the electrification of vehicles. This study focused on the coupling of Fischer–Tropsch synthesis for the production of synthetic diesel and kerosene with a high-temperature electrolysis unit. For this purpose, a process model was set up consisting of several modules including a high-temperature co-electrolyzer and a steam electrolyzer, both of which were based on solid oxide electrolysis cell technology, Fischer–Tropsch synthesis, a hydrocracker, and a carrier steam distillation. The integration of the fuel synthesis reduced the electrical energy demand of the co-electrolysis process by more than 20%. The results from the process simulations indicated a power-to-fuel efficiency that varied between 46% and 67%, with a decisive share of the energy consumption of the co-electrolysis process within the energy balance. Moreover, the utilization of excess heat can substantially to completely cover the energy demand for CO2 separation. The economic analysis suggests production costs of 1.85 €/lDE for the base case and the potential to cut the costs to 0.94 €/lDE in the best case scenario. These results underline the huge potential of the developed power-to-fuel technology.
Keywords: Process Chemistry and Technology; Chemical Engineering (miscellaneous); Bioengineering

Experimental Characterization of 3D Printed Structured Metal Packing with an Enclosed Column Wall - Riese, Julia; Reitze, Arnulf; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Additive manufacturing is a promising tool for tailored solutions in chemical engineering. This applies in particular to the design of lab‐scale packed bed columns. We present experimental results to characterize a lab‐scale 3D printed structured metal packing and compare it to a conventional counterpart. The results indicate that necessary adjustments for the manufacturing process of the metal material have an influence on important operating parameters, resulting in higher specific pressure drop, slightly higher liquid holdup and lower mass transfer efficiency.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Performance of a Laboratory-Scale Methanation Plant with Catalyst Dilution under Dynamic Operating Conditions - Herrmann, Felix; Grünewald, Marcus; Meijer, Tobias; Gardemann, Ulrich; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Assessing the demand side management potential in biofuel production; A theoretical study for biodiesel, bioethanol, and biomethane in Germany - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Biofuels, Bioproducts and Biorefining)
Abstract Minimizing the emissions produced during the processing of biofuel, one aim is to reduce or completely replace the amount of the required fossil fuels used for internal process energy. For the transition of process energy from fossil to renewable energy sources, such as solar and wind, the energy demand of biomass processing must be adjustable to the fluctuating electricity supply. The flexible adjustment of a system's power demand to follow the current power generation is commonly referred to as demand side management (DSM). This contribution shows the results of a study on the implementation of DSM in biofuel biorefineries. By identifying reference concepts that could represent biofuel production plants, the specific mass and energy consumption for the individual process steps in these reference concepts was analyzed through a literature study. The annual throughput and energy consumption of process steps in biofuel production could then be calculated, enabling the identification of the most energy‐consuming process steps. Subsequently, possible flexible operating load ranges of the respective process steps in biofuel production were identified. These findings allowed an assessment of the potential for different process units of biorefinery systems concerning the quantitative adaptability of the electricity load – the theoretical DSM potential. An approximate theoretical DSM potential of 146 MW has been identified for biofuel production in Germany. This cumulated theoretical DSM potential in biofuel production was compared to that of other industrial processes, demonstrating the magnitude and importance of the implementation of DSM in biofuel production. © 2022 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.
Keywords: Renewable Energy; Sustainability and the Environment; Bioengineering

On the lower operation limit and the gain of flexibility of an innovative segmented tray column - Fasel, Henrik; Grünewald, Marcus; Riese, Julia (Journal of Advanced Manufacturing and Processing)
Abstract Operating windows of conventional tray columns may not be large enough to ensure a sufficient separation with the current or future challenges of a volatile energy and raw material supply. Therefore, an innovative, segmented separation tray has been developed, which enlarges the operation window and thus leads to a higher flexibility, managing the challenges of higher volatility in downstream processes. In this contribution, a hydrodynamic characterization and the resulting lower operation limits of this segmented tray are presented. Furthermore, an approach to obtain shorter start‐up times for the column and a resulting faster response time to changes in the process are presented. The feasibility of this type of operation is evaluated by the investigation of the stability of the tray under new operation conditions.
Keywords: General Medicine

Options for demand side management in biofuel production: A systematic review - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Optimal design for flexible operation with multiple fluctuating input parameters - Bruns, Bastian; Grünewald, Marcus; Riese, Julia (Computer Aided Chemical Engineering)

Numerical analysis of conjugate heat transfer within internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.; Inguva, Venkatesh (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Heat transfer enhancement with internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.

Rezension zu "Helmut Simon. Leben zwischen den Zeiten. Von der Weimarer Republik bis zur Europäischen Union - Vom Bauernbub zum Verfassungsrichter und Kirchentagspräsidenten" hg. von Becker, Peter; Simon, Heide - Breckner, Anne (Jahrbuch für Evangelischen Kirchengeschichte des Rheinlandes (JEKGR))

Schöpfung, Universität und Schule - Breckner, Anne

Bericht: Tagung des Arbeitskreises für historische Religionspädagogik: Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert - Breckner, Anne

Estimation of component reliability from superposed renewal processes by means of latent variables - Rodrigues, Agatha S.; Kerschke, Pascal; Pereira, Carlos Alberto De Bragança; Trautmann, Heike; Wagner, Carolin; Hellingrath, Bernd; Polpo, Adriano (Comput. Stat.)

Sustainable and Smart Energy Systems for Europe's Cities and Rural Areas

Wissenstransfer. Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung
Der Terminus Wissenstransfer hat in den letzten Jahren verstärkt an Bedeutung gewonnen. Er bezieht sich auf die Zirkulation von Wissen zwischen Systemen, Organisationen oder Parteien, etwa zwischen Hochschulen und Gesellschaft. Damit ist nicht ‚nur‘ der Transfer wissenschaftlicher Erkenntnisse in gesellschaftliche Kontexte gemeint, sondern vielmehr - über den Erwerb und die Weitergabe von Wissen hinaus - der Dialog und die Diskursbildung zwischen Wissenschaft und Gesellschaft. Der vorliegende Band nimmt dabei entstehende Aufgaben, Herausforderungen und Chancen kulturwissenschaftlicher Forschung in den Blick. Entgegen der Annahme, Projekte aus dem Feld der Kulturwissenschaften würden im Bereich des Abstrakten verbleiben, präsentiert er Beispiele kulturwissenschaftlicher Forschung, die Theorie und Praxis berücksichtigen sowie die Verzahnung von theoretischen Erkenntnissen und ihr Mitwirken an gesellschaftlichen Diskursen verdeutlichen.

Romane der Wendeliteratur als Medien des Wissenstransfers. Eine Anstiftung zum Gespräch - Heerdegen, Björn (Wissenstransfer: Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung)

Digitalisierte Arbeitsprozesse im Hotel- und Gastgewerbe konkret: (Digitalisierungs-) Potenziale und Kompetenzanforderungen an Auszubildende - Meyer, Anja; Kirchhof, Johanna (HiBiFo – Haushalt in Bildung & Forschung)
Digitalisierte Arbeitsprozesse als Lerngegenstand dienen als Ausgangspunkt der für die Aufgabenbewältigung notwendigen Kompetenzen. Am Beispiel der Planung und Durchführung einer Veranstaltung in der Hotellerie sollen Digitalisierungspotenziale aufgedeckt und notwendige Kompetenzen zum Umgang mit diesem Arbeitsprozess herausgearbeitet werden.

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Influence of heat treatment on the suitability for clinching of the aluminium casting alloy AlSi9 - Neuser, Moritz; Böhnke, Max; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In many manufacturing areas, multi-material designs are implemented in which individual components are joined together to form complex structures with numerous joints. For example, in the automotive sector, cast components are used at the junctions of the body and joined with different types of sheet metal and extruded profiles. To be able to join structures consisting of different materials, alternative joining technologies have emerged in recent years. This includes clinching, which allows assembling of two or more thin sheet metal and casting parts by solely cold forming the material. Clinching the brittle and usually less ductile cast aluminium alloys remains a challenge because the brittle character of the cast aluminium alloys can cause cracks during the forming of the clinched joint. In this study, the influence of the heat treatment time of an aluminium casting alloy AlSi9 on the joinability in the clinching process is investigated. Specific heat treatment of the naturally hard AlSi9 leads to a modification of the eutectic microstructure, which can increase ductility. Based on this, it will be examined if specific clinching die geometries can be used, which achieve an optimized geometrical formation of the clinched joint. The load-bearing capacities of the clinched joints are determined and compared by shear tensile and head tensile tests. Furthermore, the joints are examined microscopically to investigate the influence of the heat treatment on the failure behaviour during the load-bearing tests as well as crack initiation within the joining process.
Keywords: Mechanical Engineering; General Materials Science

Influence of solidification rates and heat treatment on the mechanical performance and joinability of the cast aluminium alloy AlSi10Mg - Neuser, Moritz; Grydin, Olexandr; Frolov, Y.; Schaper, Mirko (Production Engineering)
In modern vehicle chassis, multi-material design is implemented to apply the appropriate material for each functionality. In spaceframe technology, both sheet metal and continuous cast are joined to castings at the nodal points of the chassis. Since resistance spot welding is not an option when different materials are joined, research is focusing on mechanical joining methods for multi-material designs. To reduce weight and achieve the required strength, hardenable cast aluminium alloys of the AlSi-system are widely used. Thus, 85–90% of aluminium castings in the automotive industry are comprised of the AlSi-system. Due to the limited weldability, mechanical joining is a suitable process. For this application, various optimisation strategies are required to produce a crack-free joint, as the brittle character of the AlSi alloy poses a challenge. Thus, adapted castings with appropriate ductility are needed. Hence, in this study, the age-hardenable cast aluminium alloy AlSi10Mg is investigated regarding the correlation of the different thicknesses, the microstructural characteristics as well as the resulting mechanical properties. A variation of the thicknesses leads to different solidification rates, which in turn affect the microstructure formation and are decisive for the mechanical properties of the casting as well as the joinability. For the investigation, plates with thicknesses from 2.0 to 4.0 mm, each differing by 0.5 mm, are produced via sand casting. Hence, the overall aim is to evaluate the joinability of AlSi10Mg and derive conclusions concerning the microstructure and mechanical properties.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Numerical and Experimental Investigation of Heat Transfer in the Solidification-Deformation Zone During Twin-Roll Casting of Aluminum Strips - Grydin, Olexandr; Mortensen, Dag; Neuser, Moritz; Lindholm, Dag; Fjaer, Hallvard G.; Schaper, Mirko (Light Metals 2022)

The Influence of Electrode Indentation Rate on LME Formation during RSW - Böhne, Christoph; Meschut, Gerson; BIEGLER, MAX; RETHMEIER, MICHAEL (Welding Journal)
During resistance spot welding of zinc-coated advanced high-strength steels (AHSSs) for automotive production, liquid metal embrittlement (LME) cracking may occur in the event of a combination of various unfavorable influences. In this study, the interactions of different welding current levels and weld times on the tendency for LME cracking in third-generation AHSSs were investigated. LME manifested itself as high-penetration cracks around the circumference of the spot welds for welding currents closely below the expulsion limit. At the same time, the observed tendency for LME cracking showed no direct correlation with the overall heat input of the investigated welding processes. To identify a reliable indicator of the tendency for LME cracking, the local strain rate at the origin of the observed cracks was analyzed over the course of the welding process via finite element simulation. While the local strain rate showed a good correlation with the process-specific LME cracking tendency, it was difficult to interpret due to its discontinuous course. Therefore, based on the experimental measurement of electrode displacement during welding, electrode indentation velocity was proposed as a descriptive indicator for quantifying cracking tendency.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Reduction of flange widths in resistance spot welding by application of eccentric electrode cap geometries - Böhne, Christoph; Meschut, Gerson (Welding and Cutting)

Untersuchung von Klebverbindungen für Batteriegehäuse - Schmolke, Tobias; Meschut, Gerson; Rieker, Florian; Meinderink, Dennis; Grundmeier, Guido (adhäsion KLEBEN & DICHTEN)

Untersuchung der Charakterisierung der Partikelform und deren Einfluss auf die Fließfähigkeit - Goncz, Nico; Ponusamy, SathishKumar

Untersuchung eines neuen dynamischen- mechanischen Partikelverrundungsprozesses (Studienarbeit) - Keksel, Ewald; Ponusamy, SathishKumar